Revisiting the extremely fast disc wind in a gravitationally lensed quasar APM 08279+5255 - Hagino, Kouichi; Done, Chris; Odaka, Hirokazu; Watanabe, Shin; Takahashi, Tadayuki (Monthly notices of the Royal Astronomical Society, 2017)
Abstract The gravitationally lensed quasar APM 08279+5255 has the fastest claimed wind from any active galactic nucleus, with velocities of 0.6–0.7c, requiring magnetic acceleration as special relativistic effects limit all radiatively driven winds to v < 0.3–0.5c. However, this extreme velocity derives from interpreting both the narrow and broad absorption features in the X-ray spectrum as iron absorption lines. The classic ultrafast outflow source PDS 456 also shows similar absorption systems, but here the higher energy, broader feature is generally interpreted as an absorption edge. We reanalyse all the spectra from APM 08279+5255 using a full 3D Monte Carlo radiative transfer disc wind model for the ionized wind at 0.1–0.2c, together with complex absorption from lower ionization material, and find that this is a better description of the data. Thus, there is no strong requirement for outflow velocities beyond 0.2c, which can be powered by radiation driving. We show that UV line driving is especially likely given the spectral energy distribution of this source which is intrinsically UV bright and X-ray weak. While the peak of this emission is unobservable, it must be luminous enough to power the observed hot dust, favouring at least moderate black hole spin.